SOME OBSERVATIONS ABOUT TEACHING MEDIA LITERACY (World Science, 2020)
The article highlights the civic/ role of media education that should be taught at schools and universities as a tool for educating responsible and active citizens. It emphasizes that media literacy education should be addressed in primary-secondary-tertiary education level curricula and presents examples of successful teaching and learning practices in the West which are based on competence development approach and active critical engagement of students with media. The article offers for consideration some ways to address disinformation in the classroom, analyzes conditions that make successful implementation of effective media education as well as the challenges media education experiences in Ukraine.